2016
DOI: 10.1007/s13730-016-0225-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute tumoral calcinosis due to severe hyperphosphatemia in a maintenance hemodialysis patient

Abstract: We report the case of a maintenance hemodialysis patient with severe hyperphosphatemia (26.6 mg/dL) who developed acute tumoral calcinosis. The patient started receiving maintenance hemodialysis after being diagnosed with type 2 diabetes mellitus. The patient's phosphate levels suddenly increased. He had not taken the prescribed phosphate binders for the past 5 years. He noticed swelling of the palmar aspects of his right thumb, which was diagnosed as tumoral calcinosis. His serum phosphate level reached 26.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The exact mechanism of UTC is still unknown,so no approved effective therapy currently exists.Surgery may not be the rst option due to the presence of multiple co-morbidities and higher risk of recurrence,the underlying disorder is primarily treated [30][31] .A low-phosphate diet is an essential rst step,primary treatment modalities consists of phosphate binders [32][33] and antacids, if this is ineffective,increasing urinary phosphate excretion by the administration of acetazolamide might be bene cial [34] ,this has been shown to reduce size of TC lesions to various degrees. Sevelamer may result in a decrease in serum phosphate level,but the response in the described cases in the literature was inconsistent,the bene ts are limited and it could not prevent the progression of the lesion [35] .Medical therapy is also used for TC patients,using low-calcium dialysate solutions, high-ux hemodialysis and increased length and frequency of hemodialysis treatments [36] .Fatehi et al [37] reported a case that keeping on hemodialysis improved the symptoms and reduced the mass of the lesion.Surgical resection should be considered when calcinosis causes severe pain, neurologic dysfunction or joint function limitations [38] .In addition,parathyroidectomy and renal transplantation have been performed,the role of parathyroidectomy is still controversial [39] ,it usually achieves remarkable resolution in dialysis patients with severe hyperparathyroidism and elevated serum alkaline phosphatase(ALP) [40] ,but in the absence of secondary hyperparathyroidism with a markedly elevated PTH, parathyroidectomy should be avoided as it may not improve calcium and phosphorus control or favorably affect the underlying process [41] .Successful renal transplantation can provides complete resolution of UTC by inducing a negative calcium balance [42][43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of UTC is still unknown,so no approved effective therapy currently exists.Surgery may not be the rst option due to the presence of multiple co-morbidities and higher risk of recurrence,the underlying disorder is primarily treated [30][31] .A low-phosphate diet is an essential rst step,primary treatment modalities consists of phosphate binders [32][33] and antacids, if this is ineffective,increasing urinary phosphate excretion by the administration of acetazolamide might be bene cial [34] ,this has been shown to reduce size of TC lesions to various degrees. Sevelamer may result in a decrease in serum phosphate level,but the response in the described cases in the literature was inconsistent,the bene ts are limited and it could not prevent the progression of the lesion [35] .Medical therapy is also used for TC patients,using low-calcium dialysate solutions, high-ux hemodialysis and increased length and frequency of hemodialysis treatments [36] .Fatehi et al [37] reported a case that keeping on hemodialysis improved the symptoms and reduced the mass of the lesion.Surgical resection should be considered when calcinosis causes severe pain, neurologic dysfunction or joint function limitations [38] .In addition,parathyroidectomy and renal transplantation have been performed,the role of parathyroidectomy is still controversial [39] ,it usually achieves remarkable resolution in dialysis patients with severe hyperparathyroidism and elevated serum alkaline phosphatase(ALP) [40] ,but in the absence of secondary hyperparathyroidism with a markedly elevated PTH, parathyroidectomy should be avoided as it may not improve calcium and phosphorus control or favorably affect the underlying process [41] .Successful renal transplantation can provides complete resolution of UTC by inducing a negative calcium balance [42][43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
“…As a result, hypocalcemia occurs and parathyroid hormone (PTH) is stimulated, causing hyperparathyroidism. Finally, it was found that PTH causes excessive mobilization of P and calcium from bone, resulting in vascular calcification and ectopic mass calcification [ 6 ]. On the other hand, in patients with renal dysfunction, the dysregulation of the αKlotho-FGF-receptor prevents the signaling of the P diuretic factor FGF23, resulting in hyperphosphatemia and vascular calcification.…”
Section: Discussionmentioning
confidence: 99%
“…In such patients, medical treatment may have a role. Treatment modalities such as calcium-depleted electrolytic bath [13], phosphate binders [14, 16], calcitonin, bisphosphonate [16] and diet restriction of phosphate were used to restore phosphate and calcium metabolism. This has been shown to reduce size of TC lesions to various degrees.…”
Section: Discussionmentioning
confidence: 99%